Phthalates exposure and attention- deficit/hyperactivity disorder in children: a systematic review of epidemiological literature - Praveena, Sarva Mangala; Munisvaradass, Rusheni; Masiran, Ruziana; Rajendran, Ranjith Kumar; Lin, Chu-Ching; Kumar, Suresh (Springer Science and Business Media LLC, 2020)
Epidemiological studies have proven that children mental health can be affected by environmental pollutants which are believed to be visible in the form of psychological disorder later in their childhood. Moreover, the effects of children mental health are evidently clear in the case of phthalates which have been observed to increase psychological disorder, specifically attention-deficit hyperactivity disorder (ADHD). Hence, the present study aims to conduct a systematic review and provide an overview of the existing literature on the association between urinary phthalate metabolite concentrations and ADHD symptoms among children by emphasizing the confounding factors and limitations. Additionally, this review addressed the possible phthalate mechanism insights in human body including its impact on ADHD symptoms. In this case, 16 epidemiological studies (five cross-sectional, nine cohort and two case control studies) that met all the inclusion criteria were selected out of the total of 427 papers screened to show varying quantitative associations between phthalate exposure and ADHD symptoms among children with confounding factors and limitations in the existing studies in regard to the exposure and outcomes. This review also attempted to present possible explanation on phthalate mechanism in children body and its connection on neurodevelopment and ADHD symptom development which remains unclear in most of the studies. Finally, it is highly recommended for further research to carefully design cohort studies from prenatal to later childhood development with a complete sample size in order to understand phthalate impacts on children health.